Patent policy and economic growth: A survey. (14th December 2021) - Chu, Angus C.
Abstract: This survey provides a selective review of the literature on patent policy, innovation and economic growth. The patent system is a useful policy tool for stimulating innovation given its importance on technological progress and economic growth. However, the patent system is a multidimensional system, which features multiple patent policy instruments. In this survey, we review some of the commonly discussed patent policy instruments, such as patent length, patent breadth and blocking patents, and also use a canonical Schumpeterian growth model to demonstrate their different effects on innovation and the macroeconomy.